Dictionnaire berbère tachelḥiyt - français : établi sur la base d'ouvrages publiés et non-publiés, d'études et documents divers, de thèses universitaires, d'archives, et de recherches sur le terrain, vol. 4 - Stroomer, Harry, (Handbook of Oriental Studies. Section 1 The Near and Middle East ;, 2025)
Tashelhiyt Berber is spoken in Morocco. With approximately eight to ten million speakers it is the world's largest Berber language. The lexical data for this work were collected, over almost forty years, from a great number of publications and from various archives. These data were studied and checked by the author and enriched by lexical data from the author's own fieldwork. In this dictionary Tashelhiyt Berber words and phrase are presented in alphabetic order and written in a clear Latin transcription. Meanings of words and phrases are given in French. All lexical data in this work are fully referenced. This book is the first comprehensive dictionary for Tashelhiyt Berber.